2009
DOI: 10.1103/physrevlett.102.026802
|View full text |Cite
|
Sign up to set email alerts
|

Is Graphene in Vacuum an Insulator?

Abstract: We present evidence, from Lattice Monte Carlo simulations of the phase diagram of graphene as a function of the Coulomb coupling between quasiparticles, that graphene in vacuum is likely to be an insulator. We find a semimetal-insulator transition at α crit g = 1.11 ± 0.06, where α g ≃ 2.16 in vacuum, and α g ≃ 0.79 on a SiO 2 substrate. Our analysis uses the logarithmic derivative of the order parameter, supplemented by an equation of state. The insulating phase disappears above a critical number of four-comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

44
436
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(483 citation statements)
references
References 42 publications
(44 reference statements)
44
436
3
Order By: Relevance
“…In recent years, several efforts have been made [98][99][100][101] to describe electrons moving in a honeycomb lattice and interacting through the non-relativistic Coulomb force. In this case the strength of interactions is measured by the dimensionless parameter [5,12] α ee ≡ e 2 /( hv F ), where e is the absolute value of the electron's charge, is a suitably-defined dielectric constant, and v F is the Fermi velocity.…”
Section: Long-range Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, several efforts have been made [98][99][100][101] to describe electrons moving in a honeycomb lattice and interacting through the non-relativistic Coulomb force. In this case the strength of interactions is measured by the dimensionless parameter [5,12] α ee ≡ e 2 /( hv F ), where e is the absolute value of the electron's charge, is a suitably-defined dielectric constant, and v F is the Fermi velocity.…”
Section: Long-range Interactionsmentioning
confidence: 99%
“…A excitonic insulating phase has been predicted to occur spontaneously [99][100][101] at a critical value of the Coulomb coupling constant α ee 1.1 for N f = 4 fermion flavors. Note that electrons in natural suspended graphene are characterized by α ee ∼ 2.2 (since, in this case, ∼ 1 and v F ∼ 10 6 m/s).…”
Section: Long-range Interactionsmentioning
confidence: 99%
“…[4,5,6,7,8,9,10,11,12,13,14,15,17,16]). There, the predominant ordering tendencies are in the particle-hole channel, and usually superconductivity is not among the leading candidates.…”
Section: Undoped and Weakly Doped Graphenementioning
confidence: 99%
“…González et al 3 performed renormalization-group calculations and showed that the suppression of screening of the long-range Coulomb interaction gives rise to deviations from conventional Fermi-liquid behavior. Lattice field theory simulations 4 indicated a Coulomb driven second-order semimetal-to-insulator transition. Meng et al 5 performed extensive variational quantum Monte Carlo (QMC) simulations for the Hubbard model with varying cluster sizes and identified a spin-liquid phase between the semimetallic state characterized by massless Dirac fermions and an antiferromagnetically ordered Mott insulator.…”
Section: Introductionmentioning
confidence: 99%